West Java Provincial Government's Efforts to Support Indonesian MSMEs Through Economic Diplomacy in The International Arena - Alfira Suci Mardhatillah; Muhammad Rizal Bukhori; Naufal Zamzami; Raihan Abdul Fattah (INDIEGO: Indonesian Journal of Diplomacy, Political & Economical for Global Society, 2025)
Micro, small, and medium enterprises (UMKM) in Indonesia are quite interesting to be used as a national economic structure, not only playing a role in creating jobs, UMKM can also be a common thread for economic growth. In West Java, MSMEs dominate the economic sector and are the driving force for regional economic growth, these UMKM are not only for economic growth but can also be an equal distribution of welfare, and reduce poverty. From this, efforts have emerged by the West Java Provincial Government to support Indonesian UKKM through Economic Diplomacy in the International Arena so that UMKM in West Java are increasingly advanced and well-known in the International Arena. The research method for this study is to use the Qualitative method. This study uses a review of paradiplomacy literature, and economic diplomacy theory. The efforts made by the West Java Provincial Government are by committing to increasing the competitiveness of UMKM through innovation and global market access, organizing coaching clinic programs, facilitating business matching, supporting digitalization, and paradiplomacy activities.